2015
DOI: 10.1080/01431161.2015.1030045
|View full text |Cite
|
Sign up to set email alerts
|

Variability of sea surface salinity in the tropical Indian Ocean as inferred from Aquarius and in situ data sets

Abstract: Sea surface salinity (SSS) is one of the key components of the Earth's global water cycle. Reliable information on SSS is very important for ocean modelling, data assimilation, and ocean and climate research applications. In this study, SSS variability in the tropical Indian Ocean (TIO) was analysed using the Aquarius instrument on board the SAC-D satellite and in situ observations from the Research Moored Array for African-Asian-Australian Monsoon Analysis and Prediction (RAMA) buoys and Array for Real-Time G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The numerical models have also reached reasonable level of maturity to reproduce the observed salinity fields in the tropical Indian Ocean with good accuracy , Howden and Murtugudde, 2001, Sharma et al, 2010, Parekh et al, 2015. In addition, the efforts on remote sensing of sea surface salinity (SSS) with SMOS and Aquarius are also progressing to map the global ocean surface salinity fields (Durand et al, 2013, Momin et al, 2015. So in the light of the availability of these recent measurements and numerical model outputs it is now possible to characterise and explain the nature of the observed near-surface salinity field both on intraseasonal and interannual time scales with greater confidence level.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The numerical models have also reached reasonable level of maturity to reproduce the observed salinity fields in the tropical Indian Ocean with good accuracy , Howden and Murtugudde, 2001, Sharma et al, 2010, Parekh et al, 2015. In addition, the efforts on remote sensing of sea surface salinity (SSS) with SMOS and Aquarius are also progressing to map the global ocean surface salinity fields (Durand et al, 2013, Momin et al, 2015. So in the light of the availability of these recent measurements and numerical model outputs it is now possible to characterise and explain the nature of the observed near-surface salinity field both on intraseasonal and interannual time scales with greater confidence level.…”
Section: Introductionmentioning
confidence: 93%
“…Satya Prakash et al (2012) have studied the observed relationship between surface freshwater flux and salinity in the north Indian Ocean. Momin et al ( 2015) have studied the observed variability of sea surface salinity in the tropical Indian Ocean as inferred from Aquarius and in situ data sets. Recently Zweng et al (2013) have updated the earlier climatologies to provide a comprehensive description on the salinity field of the global ocean.…”
Section: Introductionmentioning
confidence: 99%
“…The STD of the monthly mean SSS values is used as a measure of SSS seasonal variability (Figure 4). Argo shows that large STDs (>0.4 pss) dominates the following areas: the pan-tropical low salinity zone under the ITCZ and SPCZ, the near coastal areas affected by the Amazon plume in the western tropical Atlantic (Fournier, Vandemark, et al, 2017;Grodsky et al, 2014) and the Congo and Niger rivers in the eastern equatorial Atlantic (Chao et al, 2015;Reul et al, 2014), the northwestern Atlantic shelf region particularly south of the St. George's and Newfoundland banks (Grodsky et al, 2017), the northern Gulf of Mexico bordering the Mississippi (da Silva & Castelao, 2018), the vicinity of the western South Atlantic near 35°S, 55°W under the influence of the Rio de la Plata (Piola et al, 2005), the Bay of Bengal impacted by monsoon and the Ganges/Brahmaputra river (Momin et al, 2015;Fournier, Vialard, et al, 2017), and the southeastern Arabian Sea centered at 8°N, 75°E, known as the Laccadive Sea region (also called the Lakshadweep Sea) (Bruce et al, 1994;Schott & McCreary, 2001). All of these high STD regions are in direct response to the freshwater sources from rainfall and/or river discharge, except for the high STD in the Laccadive Sea of the Arabian Sea.…”
Section: Seasonal Variability Of Sssmentioning
confidence: 99%
“…The anomalously high and low SSS in the subtropical and tropical mostly coincide with sea surface freshwater flux (F) [3] . Hence, having better knowledge of the spatiotemporal variability of SSS and its covariation patterns with F is of great importance to well understanding the various processes in the coupled ocean-atmosphere dynamic [4] .…”
Section: Introductionmentioning
confidence: 99%